Techniques to derive additional information of operation actions for computer-based operating procedure. Issue 6 (3rd June 2018) - Suryono, Tulis Jojok; Gofuku, Akio
ABSTRACT: Most of the modern main control rooms of nuclear power plants are equipped with computer-based operating procedures (CBPs), which make it easier for operators to operate and control the reactor compared with paper-based operating procedure (PBP). However, most of the CBPs do not provide necessary information which is useful for operators, especially in an emergency situation. In addition, proper decisions and actions of the procedure steps are needed to prevent human errors in mitigating the accident. The additional information, which is the information of the impact of a counter action (by automatic system and human actions) such as the components influenced and future plant behavior will be very helpful for operators to understand the effects of the counter action. The aim of the study is to develop techniques to generate the additional information. Multilevel flow modeling (MFM) is applied to model a nuclear power plant and the counter actions described in CBPs. A simple emergency operating procedure of steam generator tube rupture accident of a pressurized water reactor (PWR) plant is used as a case study. The algorithm to generate the additional information is based on the influence propagation rules and cause–effect relations expressed in the MFM model of the PWR plant.